Incidence of HIV and HCV in people who inject drugs: a systematic and meta-analysis review protocol - Azam Rahmani; Zahra Jorjoran Shushtari; Asaad Sharhani; Bahram Armoon; Mehdi Noroozi; Elaheh Ahounbar; Salah Eddin Karimi; Peter Higgs (BMJ Open)
Introduction HIV and hepatitis C virus (HCV) are major health concerns globally. This systematic review and meta-analysis protocol study aims to estimate the incidence of HIV and HCV among people who inject drugs (PWIDs) by reviewing studies that have applied mathematical modelling. The primary purpose of this systematic review is to identify and review mathematical modelling studies of HIV and HCV incidence in PWIDs.Methods and analysis cohort, cross-sectional and clinical trial studies conducted to estimate the incidence of HIV and HCV based on mathematical models or have evaluated the effectiveness of mathematical models will be considered for inclusion in the review. A comprehensive search applying a Cochrane approach will be used to identify relevant primary studies, published between January 2000 and July 2020, and indexed in PubMed, EMBASE, Opengrey, WOS, SCOPUS and Cochrane Library with no restriction on language. This protocol was prepared according to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P). Study selection and data extraction will be performed by two independent reviewers. Assessment of risk of bias will be implemented using forms of the Critical Appraisal Skills Programme. Publication bias will be assessed by funnel plots, Begg’s and Egger’s tests. A meta-analysis will be conducted to answer the first research question, ‘What is the incidence of HIV and HCV when applying mathematical model in PWID?’. Clinical heterogeneity will be assessed by looking at the characteristics of participants, method of diagnosis and case definitions in the included primary studies. In addition, subgroup analyses will be conducted for population and secondary outcomes.Ethics and dissemination There are no ethical issues related to this study. The findings will be published in peer-reviewed scientific journals and presented at international and national conferences.PROSPERO registration number CRD42019126476.